Effects of norepinephrine on galanin expression in dorsal root ganglion neurons in vitro - Yang, Xiangdong (Elsevier, 2009)
Background: Norepinephrine (NE) is a key neurotransmitter that functionally activates adrenoreceptors expressed in sympathetic neurons. Functional α(1)-adrenoreceptors are also expressed in dorsal root ganglion (DRG) primary sensory neurons and regulate neurogenic inflammation and nociceptive responses. Galanin is involved in inflammation and nociception. It has been suggested that galanin receptor (GalR) 1 and GalR3 activation induces analgesia at the level of the spinal cord, while activation of GalR2 has a pronociceptive role in the periphery. Whether activation or inhibition of α-adrenoreceptors influences galanin expression remains unknown. Objective: The aim of the present study was to investigate whether the α-adrenoreceptor agonist NE, the α(1)-adrenoreceptor antagonist prazosin, and the α(2)-adrenoreceptor antagonist yohimbine affect galanin expression in primary cultured DRG neurons. Methods: DRG was dissected from 240 embryonic 15-day-old Wistar rats, cultured as dissociated cells for 2 days, and then exposed to NE (10(-4) mol/L) for another 4 days. In the NE + prazosin group and the NE + yohimbine group, DRG neurons were pretreated with prazosin (10(-6) mol/L) and yohimbine (10(-5) mol/L), respectively, 10 minutes prior to the NE challenge. The neurons cultured continuously in media served as the controls. All of the cultured samples were processed to detect galanin mRNA and galanin peptide expression by reverse transcriptase-polymerase chain reaction and Western blot, respectively. Five samples were tested for each procedure. Results: Forty samples were prepared for this study and included in the analysis. After 4 days of incubation, mean (SD) galanin mRNA/β-actin mRNA concentration ratio was significantly increased with NE compared with controls (0.3349 [0.0413] vs 0.2411 [0.0519]; P < 0.05). Pretreatment with prazosin seemed to block the effects of NE (0.2522 [0.0496]; P < 0.05 vs NE), while yohimbine did not appear to significantly alter the effects of NE on elevation of galanin mRNA/β-actin mRNA concentration (0.3154 [0.0239]; P < 0.05 vs controls). After 4 days of incubation, galanin/β-actin concentration ratio was significantly higher with NE compared with controls (0.4406 [0.0655] vs 0.2295 [0.0794]; P < 0.01). Pretreatment with prazosin appeared to inhibit NE-induced galanin peptide expression (0.3156 [0.0942]; P < 0.05 vs NE), while yohimbine did not appear to alter the effects of NE on elevation of galanin peptide concentration (0.3700 [0.0533]; P < 0.05 vs controls). Coclusions: In this small in vitro study, NE, likely due to action on α(1)-adrenoreceptors but not α(2)-adrenoreceptors, was associated with an increase in galanin mRNA concentration and galanin peptide expression in these DRG neurons. These findings might be relevant to noradrenergic pain modulation.